Cystic Neoplasms of the Pancreas: Differential Diagnosis and Radiology Correlation - Hu, Feixiang; Hu, Yue; Wang, Dan; Ma, Xiaowen; Yue, Yali; Tang, Wei; Liu, Wei; Wu, Puye; Peng, Weijun; Tong, Tong (Frontiers in Oncology, 2022)
Abstract Although the probability of pancreatic cystic neoplasms (PCNs) being detected is raising year by year, their differential diagnosis and individualized treatment are still a challenge in clinical work. PCNs are tumors containing cystic components with different biological behaviors, and their clinical manifestations, epidemiology, imaging features, and malignant risks are different. Some are benign (e.g., serous cystic neoplasms (SCNs)), with a barely possible that turning into malignant, while others display a low or higher malignant risk (e.g., solid pseudopapillary neoplasms (SPNs), intraductal papillary mucinous neoplasms (IPMNs), and mucinous cystic neoplasms (MCNs)). PCN management should concentrate on preventing the progression of malignant tumors while preventing complications caused by unnecessary surgical intervention. Clinically, various advanced imaging equipments are usually combined to obtain a more reliable preoperative diagnosis. The challenge for clinicians and radiologists is how to accurately diagnose PCNs before surgery so that corresponding surgical methods and follow-up strategies can be developed or not, as appropriate. The objective of this review is to sum up the clinical features, imaging findings and management of the most common PCNs according to the classic literature and latest guidelines.